Correction: 9, 9′-Anthryl-anthroxyl radicals: strategic stabilization of highly reactive phenoxyl radicals. Issue 24 (25th March 2015) - Aotake, Tatsuya; Suzuki, Mitsuharu; Aratani, Naoki; Yuasa, Junpei; Kuzuhara, Daiki; Hayashi, Hironobu; Nakano, Haruyuki; Kawai, Tsuyoshi; Wu, Jishan; Yamada, Hiroko
<x xml:space="preserve">Abstract</x> Correction for '9, 9′-Anthryl-anthroxyl radicals: strategic stabilization of highly reactive phenoxyl radicals' by Tatsuya Aotake et al., Chem. Commun., 2015, DOI: ; Web: 10.1039/c4cc10104a.